A LOCAL SPATIAL DATA INFRASTRUCTURE TO SUPPORT THE MERAPI VOLCANIC RISK MANAGEMENT: A CASE STUDY AT SLEMAN REGENCY, INDONESIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ABSTRACT This research aims to implement an application of a Local Spatial Data Infrastructure (SDI) for evacuation planning of Merapi Volcano disaster. The processes, problems and information flows in evacuation planning were examined. Oeo- collaboration Portal was customized in order to provide spatial resources for decision makers. It is equipped with usable maps presentation and interaction tools to support collaborative decisions. User group assessment was carried out to evaluate usability of the application. The evaluation results showed that collaborative portals on top of a local SDI can facilitate effective decision making process and improve coordination among involved stakeholders in the context of disaster preparedness and mitigation. Several aspects need to be considered in order to achieve a functional local SDI e.g. availability and quality of the spatial data, establishment of local regulations and standards, development of metadata, and strengthening capable human resources. Keywords: Local Spatial Data Infrastructure, geo-portals, user group assessment, usability.